Two Verticillium dahliae MAPKKKs, VdSsk2 and VdSte11, Have Distinct Roles in Pathogenicity, Microsclerotial Formation, and Stress Adaptation - Jun Yu (American Society for Microbiology, 2019)
ABSTRACT Verticillium dahliae causes destructive vascular wilt diseases on more than 200 plant species, including economically important crops and ornamental trees worldwide. The melanized microsclerotia enable the fungus to survive for years in soil and are crucial for its disease cycle. Previously, we found that the VdPbs2-VdHog1 (V. dahliae Pbs2-V. dahliae Hog1) module plays key roles in microsclerotial formation, stress responses, and virulence in V. dahliae. In this study, two mitogen-activated protein kinase kinase kinases (MAPKKKs) homologous to Ssk2p and Ste11p, which activate the Pbs2p-Hog1p module by phosphorylation in budding yeast, were identified in the genome of V. dahliae. Both ΔVdSsk2 (V. dahliae Ssk2) and ΔVdSte11 strains showed severe defects in microsclerotial formation and melanin biosynthesis, but the relative importance of these two genes in microsclerotial development was different. Deletion of VdSsk2, but not VdSte11, affected responses to osmotic stress, fungicidal response, and cell wall stressors. The ΔVdSsk2 strain exhibited a significant reduction in virulence, while the ΔVdSte11 strain was nonpathogenic due to failure to penetrate and form hyphopodia. Phosphorylation assays demonstrated that VdSsk2, but not VdSte11, can phosphorylate VdHog1 in V. dahliae. Moreover, VdCrz1, encoding a calcineurin-responsive zinc finger transcription factor and a key regulator of calcium signaling in fungi, was misregulated in the ΔVdSsk2, ΔVdPbs2, and ΔVdHog1 mutants. IMPORTANCE These data provide insights into the distinctive functions of VdSsk2 and VdSte11 in pathogenicity, stress adaptation, and microsclerotial formation in V. dahliae.